ANALISIS SEKTOR BASIS DAN NON BASIS TANAMAN HORTIKULTURA DALAM BIDANG SAYUR-SAYURAN KECAMATAN CURUP SELATAN, KABUPATEN REJANG LEBONG, PROVINSI BENGKULU - Muhammad Ilham Endriadi; Endah Purwaningsih (STKIP Subang, 2026)
The agricultural sector is one of the leading sectors in the development of the national economy. Agriculture in Indonesia consists of several sub-sectors, namely food crops, horticulture, livestock, and plantations. Curup Selatan District is one of the areas that contributes to the production of agricultural commodities, particularly in the horticulture sub-sector in Rejang Lebong Regency. The purpose of this study is to determine the basic and non-basic sectors in the vegetable crop commodities of the horticulture sub-sector. To identify the basic and non-basic sectors, the Location Quotient (LQ) analysis method was used. The results showed that three commodities had the highest LQ values in Curup Selatan District, namely cucumber (LQ = 2.62), long beans (LQ = 2.10), and eggplant (LQ = 1.65). In total, seven horticultural commodities were identified as belonging to the basic sector: large chili (LQ = 1.26), tomato (LQ = 1.20), eggplant (LQ = 1.65), bird’s eye chili (LQ = 1.24), long beans (LQ = 2.10), cucumber (LQ = 2.62), and chayote (LQ = 1.10). Meanwhile, seven other commodities were classified as non-basic sectors, including cabbage (LQ = 0.76), potato (LQ = 0.42), petsai (LQ = 0.78), leek (LQ = 0.64), green beans (LQ = 0.94), water spinach (LQ = 0.30), and carrot (LQ = 0.51). These findings can serve as a foundation for policymaking in the development of the horticultural sector in the region.